2023
DOI: 10.31223/osf.io/kxqsc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A prototype for a Multi-GNSS orbit combination

Abstract: Since 1994, the International GNSS Service (IGS) provides a combination of orbit and clock offset products from its different Analysis Centers. These products are used as input by many software for countless scientific and/or operational applications. They can also be used as an independent reference for benchmark experiments. Nevertheless, those products include GPS-only data, despite the fact that nowadays several GNSS constellations are available. We performed modifications on the existing IGS combination s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
(3 reference statements)
1
4
0
Order By: Relevance
“…QZSS shows the highest RMS values, which can reach around 80 mm. This behavior is also noted by Sakic et al [2020] who used an adaptation of the IGS legacy software to process the MGEX orbits. Similar results are provided by the ACC where another adaptation of the legacy software is used 4 .…”
Section: Differences Between Individual Ac Orbit Solutions and Combinsupporting
confidence: 52%
See 1 more Smart Citation
“…QZSS shows the highest RMS values, which can reach around 80 mm. This behavior is also noted by Sakic et al [2020] who used an adaptation of the IGS legacy software to process the MGEX orbits. Similar results are provided by the ACC where another adaptation of the legacy software is used 4 .…”
Section: Differences Between Individual Ac Orbit Solutions and Combinsupporting
confidence: 52%
“…The GFZ IGS working group has also been putting efforts to study and provide a dedicated and entirely consistent orbit and clock combination using the solutions provided by the ACs that contribute to the MGEX project. Previous studies were made adapting the IGS combination software [Fritsche, 2016;Mansur et al, 2020;Sakic et al, 2020], and have shown that significant modifications are needed to combine MGEX products, including an improved weighting strategy adapted to the different constellations. Therefore, only an adaptation of the existing software may not be enough to handle the different constellations with different quality of orbit solutions, as well as may not provide a full perspective about the influence that each AC has on a specific constellation.…”
Section: Introductionmentioning
confidence: 99%
“…This algorithm can also handle the different constellations separately. It corrects the weaknesses of the legacy software used routinely by the IGS's ACC, which have been raised during a preliminary study investigating the possibilities to improve it for a multi-GNSS environment (Sakic et al 2020). We tested this new algorithm with the recent set of orbit products generated by the different IGS ACs in the framework of the repro3 reprocessing campaign.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Thus, our research group has started to study a new combination strategy compatible with the new constellations, initially based on the legacy IGS software (Sakic et al 2020), then by designing an ad hoc strategy optimised for a multi-GNSS configuration (Mansur et al 2020b,a). These activities are carried out in parallel with the orbit combination studies performed by the ACC in the context of the IGS's Multi-GNSS Experiment (MGEX) pilot project (Sośnica et al 2020), and the ones regarding integer clocks (Banville et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For the combined solution of multi-GNSS orbits, two alignment methods of the orbits to ITRF using ERP and individual orbit/station coordinates, respectively, which initially obtained IGS combined multi-system orbit products [14,15]. However, in that study, all systems were treated as a whole for orbit combination, and the differences of product frame and orbit accuracy between different analysis centers or systems were ignored, maybe resulting in unreasonable weight distribution of ACs.…”
Section: Introductionmentioning
confidence: 99%